Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome